Hollow Gold-Silver Nanoshells Coated with Ultrathin SiO(2) Shells for Plasmon-Enhanced Photocatalytic Applications - Srinoi, Pannaree (Materials (Basel), 2020)
This article details the preparation of hollow gold-silver nanoshells (GS-NSs) coated with tunably thin silica shells for use in plasmon-enhanced photocatalytic applications. Hollow GS-NSs were synthesized via the galvanic replacement of silver nanoparticles. The localized surface plasmon resonance (LSPR) peaks of the GS-NSs were tuned over the range of visible light to near-infrared (NIR) wavelengths by adjusting the ratio of silver nanoparticles to gold salt solution to obtain three distinct types of GS-NSs with LSPR peaks centered near 500, 700, and 900 nm. Varying concentrations of (3-aminopropyl)trimethoxysilane and sodium silicate solution afforded silica shell coatings of controllable thicknesses on the GS-NS cores. For each type of GS-NS, scanning electron microscopy (SEM) and transmission electron microscopy (TEM) images verified our ability to grow thin silica shells having three different thicknesses of silica shell (~2, ~10, and ~15 nm) on the GS-NS cores. Additionally, energy-dispersive X-ray (EDX) spectra confirmed the successful coating of the GS-NSs with SiO(2) shells having controlled thicknesses. Extinction spectra of the as-prepared nanoparticles indicated that the silica shell has a minimal effect on the LSPR peak of the gold-silver nanoshells.